The pathogenesis, detection, and prevention of Vibrio parahaemolyticus - Wang, Rongzhi; Zhong, Yanfang; Gu, Xiaosong; Yuan, Jun; Saeed, Abdullah F.; Wang, Shihua (Frontiers in Microbiology, 2015)
Vibrio parahaemolyticus, a Gram-negative motile bacterium that inhabits marine and estuarine environments throughout the world, is a major food-borne pathogen that causes life-threatening diseases in humans after the consumption of raw or undercooked seafood. The global occurrence of V. parahaemaolyticus accentuates the importance of investigating its virulence factors and their effects on the human host. This review describes the virulence factors of V. parahaemolyticus reported to date, including hemolysin, urease, two type III secretion systems (T3SS) and two type VI secretion systems (T6SS), which both cause both cytotoxicity in cultured cells and enterotoxicity in animal models. We describe various types of detection methods, based on virulence factors, that are used for quantitative detection of V. parahaemolyticus in seafood. We also discuss some useful preventive measures and therapeutic strategies for the diseases mediated by V. parahaemolyticus, which can reduce, to some extent, the damage to humans and aquatic animals attributable to V. parahaemolyticus. This review extends our understanding of the pathogenic mechanisms of V. parahaemolyticus mediated by virulence factors and the diseases it causes in its human host. It should provide new insights for the diagnosis, treatment, and prevention of V. parahaemolyticus infection.